Peningkatan Edukasi Akupresur dalam Upaya Mengurangi Rasa Sakit Saat Haid pada Siswi SMK Bim - Isnina Isnina; Lieni Lestari; Binti Rosidah; Wilujeng M.Z (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Adolescent girls commonly experience menstrual disorders, with a 67.2% incidence of dysmenorrhea and 63.1% of premenstrual syndrome (PMS). Menstrual pain, or dysmenorrhea, is one of the most frequent reproductive health issues experienced by women, affecting both adolescents and adults. This condition can significantly hinder daily activities, which calls for appropriate treatment. Dysmenorrhea can be managed through both pharmacological and non-pharmacological methods. While pharmacological treatments offer quick relief, non-pharmacological approaches are considered safer as they do not induce side effects, unlike medications. One effective form of non-pharmacological therapy is acupressure, which has shown promising results in alleviating menstrual pain. According to a study by Latifah and colleagues, acupressure was proven to be effective in reducing menstrual discomfort. In line with this, a community outreach initiative was conducted to educate and train adolescent girls on acupressure techniques as a form of self-care. From May 5 to 9, 2025, acupressure education was provided to 30 female students at a local school. The training focused on teaching students how to apply acupressure to specific pressure points that relieve menstrual pain, without the need for medication or herbal remedies. Pre- and post-training assessments showed a significant increase in students’ knowledge and skills related to the practice of acupressure. The results indicated that students were able to effectively apply acupressure techniques and felt more confident in managing menstrual pain independently. This approach not only offered immediate relief but also empowered the students with a long-term strategy to manage dysmenorrhea in the future. This activity demonstrated positive outcomes, suggesting that acupressure is a valuable, sustainable solution for menstrual pain relief among adolescents.